Prescribed Minimum Benefits complaints: a five-year retrospective review - Lindelwa Mitchele Ngobeni; Lucky Moropeng; Evelyn Thsehla (South African Medical Journal)
Background: No matter which benefit option members have chosen, medical schemes are required by the Medical Schemes Act no. 131 of 1998 to pay costs associated with the diagnosis, treatment, or care of a specified set of benefits known as Prescribed Minimum Benefits (PMBs). Medical scheme beneficiaries have the right to lodge complaints with the Council for Medical Schemes (CMS) when their claims are denied.